The effect of sunflower oil methyl ester and diesel fuel blend on the performance of a diesel engine - Ilkilic, C. (Taylor & Francis Inc, 2008)
The viscosities of raw vegetable oils are quite higher than diesel fuel. To lower the viscosity, sunflower oil methyl ester was mixed with diesel fuel and then tested in a single-cylinder, four-stroke, air-cooled diesel engine as an alternative fuel. The study examines short-term engine tests with sunflower oil methyl ester fuel compared to number 2 diesel fuel (No. 2 D). Engine tests were carried out fully loaded at different speed ranges. The engine torque and power of sunflower oil methyl ester-diesel fuel blend was lower than that of diesel fuel in the range of 6-9%, and specific fuel consumption was higher than that of diesel fuel by approximately 3%. CO2, CO, and NOx emissions of sunflower methyl ester were lower than those of diesel fuel.
Keywords: alternative fuels; diesel fuel; emission; sunflower oil methyl ester